A Feedback Loop Involving MicroRNA-150 and MYB Regulates VEGF Expression in Brain Microvascular Endothelial Cells After Oxygen Glucose Deprivation - Zhang, Song; Chen, Anqi; Chen, Xiaolu (Frontiers in Physiology, 2021)
Vascular endothelial growth factor (VEGF) plays a pivotal role in regulating cerebral angiogenesis after stroke. Meanwhile, excessive VEGF expression induces increased microvascular permeability in brain, probably leading to neurological deterioration. Therefore, the appropriate level of VEGF expression is significant to the recovery of brain exposed to stroke. In this work, we demonstrate that microRNA-150 (miR-150) and its predicted target MYB form a negative feedback loop to control the level of post-stroke VEGF expression. Repression of MYB leads to decreased expression of miR-150 in brain microvascular endothelial cells (BMVECs) exposed to oxygen glucose deprivation (OGD), thus miR-150 was predicted to be down-regulated by MYB. Moreover, MYB was confirmed to be a direct target of miR-150 by using dual luciferase reporter assay. In our previous work, we have validated VEGF as another direct target of miR-150. Therefore, MYB participates in regulation of VEGF via miR-150 under OGD, forming a feedback loop with miR-150. We also find that high levels of miR-150 inhibitors combined with MYB silence contribute to further enhancement of VEGF expression in BMVECs in response to OGD. These observations suggest that the feedback loop comprised of miR-150 and MYB, which is a pivotal endogenous epigenetic regulation to control the expression levels of VEGF in BMVECs subjected to OGD.